Tablični računalnik - majhno orodje, velik izziv - Fidler, Tomaž (Šolska knjižnica, 2012)
The paper presents tablet computers and emphasizes four best sold models in the USA: Kindle Fire, Samsung Galaxy Tab 2 7.0, iPad,and Asus Eee Pad Transformer Prime with a mobile dock keyboard. We expect that tablet computers will become a valuable electronic tool also in schools. In April 2012 we performed an anonymous survey among primary and secondary school students to find out if they are familiar with these comouters and their use.
Keywords: digitalna pismenost; IKT; informacijsko-komunikacijska tehnologija; osnovne šole; srednje šole; tablični računalniki; učni pripomočki